Anterior Cruciate Ligament (ACL) Injuries: Modern Strategy of Surgical Treatment (Review) - Skobenko, Ye.O.; Kvasha, V.P.; Kuprii, V.O. (TERRA ORTHOPAEDICA, 2021)
Summary. Of all knee injuries, the most common one is the anterior cruciate ligament (ACL) injury. The ACL plays a key role in the stability of the knee joint: it limits the anterior dislocation of the tibia and ensures the stability of rotational movements. In physically active patients, surgical reconstruction of the ACL injury is the gold standard of treatment. The development of biomechanical, biological, clinical research, and tissue engineering provides the basis for disagreement about the methods of reconstruction of ACL injuries. This review outlines modern approaches to the surgical treatment of the ACL.